Consumption of evaporated milk of household level in Central Java - Widiyanti, Rahayu; Mastuti, Sri (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2002)
The objective of the research was identity factors affecting consumption of evaporated milk at household level in Central Java. Data obtained were the primary data of SUSENAS for Central Java in the years of 1993, 1996 and 1999, which were collected by BPS. Sampling method occupied was statified proportional random sampling. Out of 20.600 household populations, 600 units were taken as samples. Sencoric data of SUSENAS were analyzed by using Tobit model, estimating method of maximum likelihood estimation (MLE) was applied. That was concluded that consumption of evaporated milk were influenced by its own price, price of milk powder, education of the mother, family income, place the family live, and environmental factor. Evaporated milk was treated as luxurious consumption. (Animal Production 4(1): 21-26 (2002)Key words : Consumption, evaporated milk, tobit.